Microstructure and its effect on high temperature tensile properties of T92/HR3C dissimilar weld joints. (October 2022) - Wang, Qibing; Xin, Ruishan; Wang, Zhichun; Han, Zhewen; Jiao, Xiangdong; Kang, Ju
Abstract: A T92/HR3C dissimilar metal weld joint, which is widely used in the boiler components of ultra-supercritical power plants, was fabricated by manual tungsten inert gas welding with Inconel 82 as the filler metal. This study reports the high-temperature tensile properties, deformation behavior, and fracture mechanism of dissimilar weld joints. The results of tensile tests at 640 °C show a severe strength mismatch between the weld metal and the heat-affected zone of the T92 steel (T92-HAZ). The serrated flow behavior of the T92/HR3C weld joint at different tensile rates was observed during plastic deformation. Based on the results of transmission electron microscopy, dynamic recrystallization and re-precipitation of Cr23 C6 carbides both likely triggered the serrated flow behavior and enhanced the tensile strength of the weld metal. Additionally, the inter-critical T92-HAZ was the weakest zone in the weld joint because of the dissolution of a large amount of carbides and the transformation of martensite laths into equiaxed subgrains.